Exploring Thematic Structures and Progression in Self-Help Literature: A Textual Metafunction Analysis of “The 5 Second Rule” - Putri, Gusti Agung Mira Diana; Ayomi, Putu Nur (Lembaga Penelitian dan Pemberdayaan Masyarakat (LITPAM), 2024)
Given the widespread appeal and influence of self-help literature, understanding how authors engage and inform their readers through linguistic strategies is crucial. The study aims to explore how thematic structures contribute to the genre’s purpose of motivating and guiding readers. A descriptive qualitative method was employed, involving observation, interpretation, and explanation. The analysis reveals that the most frequent Themes in the text are Unmarked Topical Themes, primarily in the forms of “You,” “I,” and “It.” The text also frequently utilizes Conjunctive Adjuncts as Textual Themes (e.g.,